Prevalence of Anaplasmosis in cattle in Sirajganj district of Bangladesh - Belal, SM Shariful Hoque; Mahmud, Md. Abdullah Al; Ferdous, Mst Jannatul (Research in Agriculture Livestock and Fisheries, 2015)
An epidemiological investigation was conducted to ascertain the prevalence of anaplasmosis in cattle in Sirajganj district of Bangladesh, during the period of December 2013 to November 2014. During one year study period a total of 395 cattle were examined, and where 102 were found to be infected with Anaplasma spp. On Geimsa stained blood smear examination, it was observed that the overall prevalence of anaplasmosis in cattle was recorded as 25.82%. The effect of area, age, sex, breed and season was observed in cattle during this study. The highest prevalence (34.19%) was reported in the older cattle (> 3 years of age) and the prevalence was higher in female (28.88%) than male (19.20%). All crossbred cattle was showed higher prevalence than local cattle. The prevalence of anaplasmosis infection was noticed as the highest in the rainy season (30.68%) in relation to summer (27.50%) and winter (15.15%) season. From the study it was evident that cattle were infected with the organism and caused a serious economic loss which will assist to take necessary preventive interventions. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22370 Res. Agric., Livest. Fish.1(1): 97-103, Dec 2014